The Big Three Allies and the European resistance : intelligence, politics, and the origins of the Cold War, 1939-1945 - Piffer, Tommaso 1981- (Oxford University Press, 2024)
"A comparative and pan-European study of the Big Three's involvement in Resistance movements across wartime Europe. From Yugoslavia to Poland and from Greece to France and Italy, the book vividly depicts and sharply analyses how this proxy war shaped the history of the post-war settlement."